Coupled mutations-enabled glycerol transportation in an aquaporin Z mutant - Ping, Zhi (2019)
Aquaporins are transmembrane channel proteins with key function being transportation of water or other small substrates. Escherichia coli Aqp Z transports water molecules only, whereas Glp F is permeable to glycerol. It is intriguing to explore the possibility to induce glycerol permeability in Aqp Z by targeted mutations. The Aqp Z mutants with mutated selectivity filter (SF) residues exhibit poor permeability for both glycerol and water. For addressing the complexity of protein systems, pair correlation information in protein sequence analyses is instructive to identify residues that are coupled by coevolution and motion. In this study, we analyze the correlation between residues and unravel the clustering patterns of coupled residues, beyond SF residues, in aquaglyceroporins (AQGPs). The identified coupled motifs are proposed to be sequenced into aquaporin (Aqp Z) to introduce glycerol permeability. These residues are located in the vicinity of SF region, C-loop, and M6–M7 linkage domain. Significant enlargement of SF pore size of the proposed Aqp Z mutant is observed by an all-atom replica exchange molecular dynamics simulation, which is critical to facilitate considerable glycerol passage as characterized in calculated free-energy landscapes. Clearly, the hidden connections among residues play crucial roles in water/glycerol selectivity. In contrast, single-site mutation-based scheme may even lead to undesirable effects in AQGPs, such as the blocking of water transportation by aromatic π-stacked gate. As demonstrated in this work, the pair correlation analysis guided rational mutagenesis provides a feasible strategy to modulate proteins’ functions.